Binding of Toxoplasma gondii Glycosylphosphatidylinositols to Galectin-3 Is Required for Their Recognition by Macrophages - Debierre-Grockiego, Françoise (American Society for Biochemistry and Molecular Biology, 2010)
We showed that the production of tumor necrosis factor (TNF) α by macrophages in response to Toxoplasma gondii glycosylphosphatidylinositols (GPIs) requires the expression of both Toll-like receptors TLR2 and TLR4, but not of their co-receptor CD14. Galectin-3 is a β-galactoside-binding protein with immune-regulatory effects, which associates with TLR2. We demonstrate here by using the surface plasmon resonance method that the GPIs of T. gondii bind to human galectin-3 with strong affinity and in a dose-dependent manner. The use of a synthetic glycan and of the lipid moiety cleaved from the GPIs shows that both parts are involved in the interaction with galectin-3. GPIs of T. gondii also bind to galectin-1 but with a lower affinity and only through the lipid moiety. At the cellular level, the production of TNF-α induced by T. gondii GPIs in macrophages depends on the expression of galectin-3 but not of galectin-1. This study is the first identification of a galectin-3 ligand of T. gondii origin, and galectin-3 might be a co-receptor presenting the GPIs to the TLRs on macrophages.